Perceived difficulty levels of basic concepts in biology by teachers in senior schools in Ogbomosho, Nigeria - Alawonde, Oluseye Adegboye; Luwoye, Akindeyi; Ahmed, Abiola Tawa; Ahmed, Mulkah Adebisi; Abimbola, Ahmatullahi Folakemi (Department of Biology Education, Universitas Pendidikan Indonesia, 2024)
Over the years, many factors have been visible that lead to unimpressive performance in biology. One of the factors includes ineffectiveness and inefficiency of biology teachers which results from the difficulties faced with some biology concepts. The study investigated perceived difficulty levels of basic concepts in biology by teachers in senior schools in Ogbomosho, Oyo State. The study adopted a descriptive research of the survey type. The population for this study comprised all biology teachers in Ogbomosho. A simple random sampling technique was employed to select 262 respondents. The research instrument for this study was the Biology Teachers’ Perceptions Questionnaire on Difficult Concepts (BTPQDC). Three research questions were raised in the study. The research questions were analyzed using frequency count, percentage and cross-tabulation. The results showed that biology teachers perceived the majority of the basic concepts as not difficult. The concepts include the conservation of energy topics such as laws of thermodynamics, food chain, water cycle, micro and macro elements and holozoic nutrition Also, biology teachers perceived some reasons as the cause of difficulty in the basic concepts of biology. They include misconception of the concepts, insufficient subject-matter knowledge of the concepts, abstractness of the concepts, and complexity of the topic.